Numerical simulation of particulate suspension transport and permeability impairment in an actual rough fracture under normal stresses. Issue 4 (12th December 2019) - Zhu, Baiyu; Tang, Hongming; Zhao, Feng; Tang, Haoxuan
Abstract: The transportation and capture of particulate suspension in a rough fracture are widely encountered in hydrocarbon exploitation. According to a full review of the literature, traditional studies mainly focus on the placement and settlement of coarse particles such as proppants and lost circulation materials. Furthermore, a fracture is often considered to be equivalent to smooth parallel plates, whereas actual fractures are roughly walled with microconvex and are affected by normal stresses. The particulate suspension transport mechanism in a fracture under different normal stresses is still unclear. This paper proposes an approach to evaluate the permeability impairment caused by size‐exclusion of solid particles in a fracture under different normal stresses. The morphology of fracture flow space under different normal stresses is obtained by using optical scanning and FEM. Furthermore, the unresolved CFD‐DEM method is used to study the mechanism of the capture and migration of the particulate suspension in a fracture. The simulation results are in agreement with the experimental results. Furthermore, the effects of the particle size, particle concentration, injected particle volume, fracture occurrence, and applied pressure on particle invasion are discussed. Abstract : An approach to evaluate permeability impairment caused by solid particle size‐exclusion in fracture under different normal stresses is proposed. The effects of particle size, particle concentration, injected particle volume, fracture occurrence, and applied pressure on particulate suspension transport and capture are discussed.